A temporal investigation into butterfly kick placement following a breaststroke star and turn - McCabe, C.; Mason, B.; Fowlie, J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to determine whether an early or late placement of the butterfly kick during the arm pull-down is more effective in terms of breaststroke start and turn performance between female and male swimmers. Overall the timing of the kick placement does not appear to influence the effectiveness of the underwater phase following a breaststroke start or turn. Therefore the style selected by swimmers may be as a result of individual preference. Females overall start performance was improved by using an early placement.